Effect of Information Technology on Organizational Performance at Yemeni Oil Exploration–Production Company - Baligh Al Haj; Naelati Tubastuvi; Dheya Alhag Alsharabi (Universitas Muhammadiyah Purwokerto, 2025)
This research paper examines the influence of six essential information technology factors; human resource capabilities, devices and equipment, communication networks, software applications, databases, and information security on organization performance in the Yemeni Oil Exploration and Production company, a situation that is characterized by political instability and limited resources. By using the constructs of perceived usefulness and perceived ease of use of the Theory of Technology Acceptance Model, a cross-sectional survey of 202 employees, who were selected using stratified-random sampling process, was conducted. Questionnaires collected the data and were thoroughly validated and analyzed based on a descriptive analysis, classical assumption test, and multiple regression. Results show that the strongest positive short-term predictors of operational efficiency, speed of decision-making, service quality, and financial results are communication networks (β = 0.442, p < .001), databases (β = 0.216, p < .001), and human resource skills (β = 0.185, p < .001). There is also a positive contribution of software (β = 0.067, p<.01) and information security (β = 0.056, p<.05) and together they explain 68.6% of the variance in performance (Adjusted R² = 0.686) Devices and equipment, on the contrary, showed a small negative influence (β = – 0.078, p < .05) which shows that mere acquisition them without proper planning might not be effective. Such findings highlight the importance of ensuring strong communication infrastructures and user-focused adoption projects within resource-poor, unstable environments and provides easily applied advice on IT investment and capacity-building projects in such environments.